Weak-Form and Semi-Strong-Form Stock Return Predictability Revisited - Ferson, Wayne E.; Heuson, Andrea; Su, Tie (Management Science, 2005)
This paper makes indirect inference about the time variation in expected stock returns by comparing unconditional sample variances to estimates of expected conditional variances. The evidence reveals more predictability as more information is used, and there is no evidence that predictability has diminished in recent years. Semi-strong-form evidence suggests that time variation in expected returns remains economically important.